Modeling Monetary Transmission in Switzerland with a Structural Cointegrated VAR Model - Katrin Assenmacher-Wesche (Swiss Journal of Economics and Statistics, 2008)
This paper examines the transmission of monetary policy in Switzerland using a structural vector error correction model (SVECM) that includes real money, real output, a long and short-term interest rate, inflation and the exchange rate as endogenous variables; and a foreign interest rate and oil prices as exogenous variables. The SVECM takes account of five cointegrating relations that are interpreted as capturing money demand, the real interest rate, the term spread, uncovered interest parity and an aggregate-demand schedule. After identifying a monetary policy shock, the model is used for impulse-response analysis. We find that including money in the model eliminates the price puzzle often found in the VAR literature. Moreover, it produces monetary policy shocks that are about three times smaller and much less persistent as in versions of the model without money. In addition, the long-run structure imposed by cointegration leads to a quicker return to equilibrium after a shock.
Keywords: E40; C32; 330; Monetary transmission; structural vector error correction model